Evaluation of anxiolytic effect of elaeocarpus ganitrus in mice - Rauniar, G P; Sharma, M (Health Renaissance, 2012)
Background: Antianxiety drugs are prescribed frequently and associated with several limitations factors that led to interest in the alternative remedies. Herbal drugs are used in developing and developed countries but there is lack of scientific evidence. Ayurvedic physician were used Elaeocarpus ganitrus for the treatment of mental calmness. Objectives: Evaluate the anxiolytic effect of Elaeocarpus ganitrus in mice. Methods: The experimental study was conducted with the extract of Elaeocarpus ganitrus in comparison with Diazepam 1mg/kg in 60 mice using open field test and passive avoidance apparatus in six experimental groups. The data were analyzed using Mann-Whitney test and P<0.05 was considered statistically significant. Results: There was a significant increase in number of square crossed, time spent in central square and rearing behavior of animal. There was also decreased significantly time prolongation in Step down latency and increase of attempts in step down errors as well as time spent in the shock zone. Conclusion: Elaeocarpus ganitrus showed anxiolytic effect but there is need to find out safety, efficacy and the exact mechanism of action of this herbal remedies. DOI: http://dx.doi.org/10.3126/hren.v10i2.6575 Health Renaissance 2012; Vol 10 (No.2); 108-112